Developing Reading Material for Architecture Student at National Institute of Technology - Rini Anjarwati (Language-Edu, 2020)
Teaching material has a vital role in the process of teaching and learning. It is so important of a component that may not be neglected since the success in obtaining the maximum input of the knowledge depends on the proper selection of the teaching material. Moreover, in the attempt of designing the teaching material relevant to the learner needs, a need analysis is conducted. By fulfilling the learner needs, learning becomes meaningful and purposeful. The purpose of this study was to conduct a need analysis for architect students in National Institute of Technology Malang aiming at developing a reading material. A questionnaire was adopted as the method of needs analysis, prior to collecting the data, literature was reviewed. In total, 52 architecture students, 20 alumni of architecture students, 20 professional architects participated in this study. The finding of this study provided valuable implication for researchers to develop teaching material.Keywords: teaching material, reading, need analysis, designing